Effect of pharmacist intervention on medication adherence and clinical outcomes of type 2 diabetes mellitus outpatients in primary healthcare in Indonesia - Nani Apriani Besemah; Ratu Ayu Dewi Sartika; Rani Sauriasari (Wolters Kluwer Medknow Publications, 2020)
Objective: In Indonesia, the role of pharmacists in primary healthcare is still very limited or even absent. This study evaluates the effectiveness of programs delivered for type 2 diabetes mellitus (T2DM) patients by pharmacists in primary healthcare through counseling, short message service (SMS) reminders, and medication booklets. Methods: A quasi-experimental study with a pretest-posttest design was conducted from April to August 2018 at Merdeka and Dempo primary health-care centers, Palembang, South Sumatra Province, Indonesia. Counseling and medication booklets were distributed three times during the study period, while SMS reminders were sent once a week. Counseling was given for the management of diabetes mellitus (DM), including during the Ramadan fasting period, together with management for acute and chronic complications. The medication adherence level was measured using a medication adherence questionnaire (MAQ) and pill count adherence (PCA). The study sample comprised 80 T2DM patients, who were allocated into either the control group (CG) (n = 40) or intervention group (IG) (n = 40). Clinical outcomes were determined by measuring glycated hemoglobin (HbA1c), blood pressure, and lipid profiles. Findings: After the intervention, the IG showed significant improvements in most parameters, except for high-density lipoprotein cholesterol and systolic and diastolic blood pressure. HbA1c levels were reduced, while MAQ scores and PCA scores were improved. Lipid parameters were significantly reduced total cholesterol (TC), low-density lipoprotein cholesterol (LDL-c), and triglyceride (TG). Compared with the CG, most parameters were significantly improved in the IG. Pharmacist counseling significantly improved almost all clinical parameters (HbA1c, TC, LDL-c, and TG). Pharmacist counseling was 7.1 times greater in lowering HbA1c compared with no counseling, after adjusted by other variables. The variable that most influenced the lowering of HbA1c was infrequent ("not often") consumption of unhealthy foods (OR 14.9; 95% CI 3.5-63.7). Conclusion: The pharmacist primary health-care intervention program implemented in this study significantly improved HbA1c, TC, LDL-c, TG, and medication adherence in outpatients with T2DM.